Information Needs among Parents of Cancer Children: A Systematic Review - Nurhidayah, Ikeu; Nani Nurhaeni; Isna Hanifah; Allenidekania Allenidekania (Universitas Airlangga, 2024)
Background: When a child is diagnosed with cancer, parents are affected, especially if they are unprepared and do not understand the illness. Parents' informational needs are frequently expressed and vary, so identifying parent needs is critical before providing health or nursing interventions. Aims: This review aimed to identify the information needs of parents of children with cancer. Method: PubMed, Medline, and CINAHL were applied to conduct electronic searches. The terms